Effectiveness of topical tacrolimus treatment in vitiligo patients (Central Medical College Journal, 2023)
Background: Vitiligo is an acquired, pigmentary skin disorder that is disfiguring and difficult to treat. Phototherapy and the application of topical corticosteroids are most commonly prescribed. However, these therapies are often not effective and the use of corticosteroids on the face may lead to cutaneous atrophy, telangiectasia, and ocular complications.Objective: To evaluate the effectiveness of topical tacrolimus treatment in vitiligo patients.Materials and methods: This prospective, randomized control trial study was conducted among the patients who sought health care in the Dermatology and Venereology out patient department of KYAMC, Enayetpur, Sirajgonj from August 2021 to July 2022. The study was conducted with a view to evaluate the efficacy of topical tacrolimus in vitiligo and to see the adverse effects of topical tacrolimus in the treatment of vitiligo.Results: This study shows 70 patients were enrolled them 32 were male and 38 were female. The mean age was 28.52±10.98 years. Monthly evaluations were performed. Maximum 61 patients (87.1%) achieved varying levels of repigmentation. 28 patients (40.0%) had reported up to 50% repigmentation. Sign and symptoms of erythema (8.6%) and burning (7.1%) were minimal.Conclusion: This study revealed that tacrolimus ointment may be an effective and safe option for the treatment of vitiligo. The ease of topical self-administration with minimal side effects makes this novel immunomodulatory agent a promising addition to the therapeutic armamentarium for vitiligo.Central Medical College Journal Vol 6 No 1 January 2022 Page: 44-48